The Effect Of Company Size And Company Age On Financial Performance Of Banks Listed On The Indonesia Stock Exchange In 2024/2025 - Yusril Ihza Mahendra (CV Edujavare Publishing, 2026)
The Effect Of Company Size And Company Age On Financial Performance Of Banks Listed On The Indonesia Stock Exchange In 2024/2025